Post-natal Growth Retardation Associated With Impaired Gut Hormone Profiles, Immune and Antioxidant Function in Pigs - Qi, Ming; Tan, Bie; Wang, Jing; Liao, Simeng; Li, Jianjun; Liu, Yanhong; Yin, Yulong (Frontiers in Endocrinology, 2019)
The reasons that cause the postnatal growth retardation (PGR) are complicated in pigs. Metabolic and immune system should be impaired in PGR pigs. The purpose of this study was to investigate the changes of blood parameters, hormone profiles, antioxidant capacity and immune responses in PGR pigs. Blood and small intestinal mucosa samples were collected from 42-d-old PGR and healthy pigs. The results showed that compared with healthy group, the relative weight of spleen and kidney were greater, but the liver were lighter in PGR pigs (P < 0.05). The PGR pigs had increased serum alanine transaminase, urea nitrogen, blood ammonia, IgG, and complement 4, while decreased glucose and albumin (P < 0.05). The higher levels of serum leptin (LEP) and thyroxin (T4), and the lower levels of insulin like growth factor-1 (IGF-1), 5-hydroxytryptamine (5-HT), somatostatin (SS), and agouti gene-related protein (AgRP) were observed in PGR pigs (P < 0.05). Consistent with the serum levels of hormones, the mRNA levels of gut hormones and their receptors were also altered in intestinal mucosa from PGR pigs (P < 0.05). The PGR pigs exhibited higher plasma concentrations of interleukin-1β (IL-1β), IL-6, IL-8, and transformed growth factor beta (TGFβ) (P < 0.05). However, the mRNA expressions of several cytokines were lower in the small intestinal mucosa of PGR pigs (P < 0.05). The abnormal antioxidant indexes in serum of PGR pigs were observed, which was in accordance with the reduced mRNA expression of several anti-oxidative genes in the small intestinal mucosa of PGR pigs (P < 0.05). These data demonstrate that the abnormal gut hormone system, immune dysfunction, and decreased antioxidant capacity may contribute to PGR in pigs. These changes could provide valuable target in regulation of postnatal growth retardation in animal and human.